2013
DOI: 10.1007/s12264-013-1302-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 5-HTTLPR genotypes on structural and functional connectivity within amygdala-prefrontal cortex circuitry

Abstract: Anxiety and depression are highly heritable disorders that lead to significant impairment in affected individuals across gender, ethnicity and race; these disorders are frequently the leading causes of disability and suicide in many countries. One could assume that the same pathophysiological mechanisms underlie anxiety and depression in all affected individuals; however, the observed clinical heterogeneity within these disorders raises doubts and questions as to the validity of this assumption. Moreover, no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The reward prediction error hypothesis cannot explain the selectivity of DA neurons for different directions of motion (Figure 3 ), the linear relationship between DA activity and kinematic variables independent of reward (Figure 6 ), the high correlation between DA activity and movement on appetitive and aversive trials (Figure 7 ), the lateralization of leftward and rightward selective neurons on the two sides of the brain (Figure 9 ), and the observation that DA activity reflects the mathematical derivative of the GABAergic SNr output (Figure 13 ). Nor can it explain previous observations on locomotion (Wang et al, 2013 ), posture control (Barter et al, 2014 ), motivational modulation (Rossi et al, 2013a ), or instrumental actions (Jin and Costa, 2010 ; Fan et al, 2012 ). Yet, as we shall see below, all these results can be explained by the crucial role of DA in shaping movement kinematics.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The reward prediction error hypothesis cannot explain the selectivity of DA neurons for different directions of motion (Figure 3 ), the linear relationship between DA activity and kinematic variables independent of reward (Figure 6 ), the high correlation between DA activity and movement on appetitive and aversive trials (Figure 7 ), the lateralization of leftward and rightward selective neurons on the two sides of the brain (Figure 9 ), and the observation that DA activity reflects the mathematical derivative of the GABAergic SNr output (Figure 13 ). Nor can it explain previous observations on locomotion (Wang et al, 2013 ), posture control (Barter et al, 2014 ), motivational modulation (Rossi et al, 2013a ), or instrumental actions (Jin and Costa, 2010 ; Fan et al, 2012 ). Yet, as we shall see below, all these results can be explained by the crucial role of DA in shaping movement kinematics.…”
Section: Discussionmentioning
confidence: 85%
“…Although we cannot rule out this possibility, classic studies from monkeys concluded that DA neurons from both SNc and VTA have similar phasic responses in relation to behavioral events (Schultz, 1998a ). In addition, recent studies also found a strong correlation between VTA activity and movement (Puryear et al, 2010 ; Wang and Tsien, 2011b ; Wang et al, 2013 ). It remains to be seen whether VTA DA neurons also represent movement kinematics.…”
Section: Discussionmentioning
confidence: 91%
“…Infusion of actin cytoskeleton assembly inhibitors into the amygdala impaired the consolidation and reconsolidation of fear memory (Rehberg et al, 2010 ), and blocked the reacquisition when re-exposed to the US at the last extinction session (Motanis and Maroun, 2012 ). In addition, the synaptic plasticity is modulated by actin cytoskeleton, including the orchestration of the pre-synaptic vesicle cycle and the organization and trafficking of postsynaptic receptors (Kuriu et al, 2006 ; Xu and Wang, 2013 ; Gordon-Weeks and Fournier, 2014 ). Rac1 regulates dendritic spine morphogenesis, which is required for synaptic plasticity, through the modulation of actin cycling (Kennedy et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown fear conditioning involves integration of CS and US inputs in the lateral amygdala (LA) and fear memory is stored in the basal amygdala (BA; Long et al, 2013 ) . The alterations in signaling and synaptic plasticity in the basolateral amygdala (BLA, composed of LA and BA) encode key aspects of the fear learning (Schafe et al, 2001 ; Long et al, 2013 ; Xu and Wang, 2013 ). Fear conditioning involves different stages of memory.…”
Section: Introductionmentioning
confidence: 99%
“…This is also true of dedicated body configuration (gait) controllers for stereotyped behaviors like locomotion. Striatal activity and DA modulation are critical for regulating the speed of locomotion (Wang and Tsien, 2011; Wang et al, 2013; Kim et al, 2015; Rueda-Orozco and Robbe, 2015; Roseberry et al, 2016).…”
Section: Da and Gain Controlmentioning
confidence: 99%